МОДЕЛЮВАННЯ ХМАРНОГО ПОКРИВУ НА ОСНОВІ СУПУТНИКОВИХ ЗНІМКІВ - Клен, К.С.; Мартинюк, В.І.; Жуйков, В.Я. (Інститут електродинаміки Національної академії наук України, 2020)
The article discusses the method of creating a cloud cover model for modeling the operation of a solar power plant, taking into account the spatial location of the station and weather conditions. The resulting model can be used to simulate various subsystems of solar power plants under conditions close to real ones. An algorithm for increasing the resolution of images of meteorological satellites is presented. An algorithm for using random walks to introduce a random component into the resulting image is presented. It is shown that the introduction of a random component does not change the initial value of the absorption coefficient of solar radiation. References 7, fig. 3.